Applications of Hybrid Metal Nanoparticle-Quantum Dot in Biomedical Applications - Akram, Haneen; Muwaffaq Abdullah,; Feddi, E.; Al-Khursan, Amin; Laura Milena Pérez,; M. Kria, (University of Thi-Qar Journal of Science, 2023)
Nanomaterials are at the forefront of the fast-paced development of nanotechnology. These materials are outstanding and indispensable in various human activities as long as their size-dependent characteristics. One of the most promising applications of nanomaterials is biomedical. This work reviews the hybrid quantum dot-metal nanoparticle applications in biomedical. An analytical model for the double quantum dot